Ceftolozane/tazobactam use and emergence of resistance: a 4-year analysis of antimicrobial susceptibility in Pseudomonas aeruginosa isolates in a tertiary hospital - Alessandra Imeneo; Laura Campogiani; Laura Campogiani; Pietro Vitale; Andrea Di Lorenzo; Andrea Di Lorenzo; Grazia Alessio; Davide Natale Abate; Maria Grazia Celeste; Anna Altieri; Cartesio D’Agostini; Cartesio D’Agostini; et al. (Frontiers in Microbiology)
BackgroundCeftolozane/tazobactam (C/T) was temporarily withdrawn from December 2020 to February 2022: this forced unavailability created the conditions to study how drug discontinuation might influence Pseudomonas aeruginosa (PA) resistance reversibility in a real-life setting.MethodsClinically relevant PA isolates collected between January 1st 2019 and February 22nd 2023 with a C/T susceptibility test available were included. Changes in PA antibiotic susceptibility towards C/T and other antibiotics were examined in three different periods (period A, March–December 2019 and March–December 2020, C/T available; period B, March–December 2021, C/T withdrawn; period C, March–December 2022, C/T reintroduced), also considering the overall consumption rate through the Defined Daily Dose per 100 bed-days per year.ResultsSeven hundred and fifty-one PA isolates were included. A statistically significant reduction of C/T resistance rate was observed when C/T became unavailable, followed by a subsequent increase with its reintroduction (period A 25.1% vs. period B 5.3% vs. period C 10.0%, p < 0.001). A concomitant reduction of resistance rates towards other antibiotics was recorded, consistent with antibiotic consumptions and antimicrobial stewardship programs implementation. A subgroup of 22 patients presented a C/T-resistant isolate after a previous susceptible one; only 4 patients had received a prior C/T treatment.ConclusionThe unavailability of C/T created the conditions to analyze the practical application of the theory of fitness cost to maintain resistance. A subsequent increase after a first reduction in C/T resistance rate was observed, probably due to persistence of resistant isolates and antibiotic selective pressure. Continuous monitoring of antibiotic use and evolving resistance is essential.